URBAN RESIDENTS' ATTITUDES TOWARD WILDLIFE IN THEIR NEIGHBOURHOODS: THE CASE STUDY OF KLANG VALLEY, MALAYSIA - Nik Mohamad, Nik Hanita (PLANNING MALAYSIA, 2011)
Rapid urbanisation in Malaysia has resulted in the loss and fragmentation of lowland tropical forests. Due to the modification ofhabitat needs provided by these natural green, the diversity and population of urban wildlife have been significantly reduced. Urban parks provided are recognized as an effective urban conservation strategy to mitigate the effects of urbanisation by conserving, enhancing and creating new habitats for urban wildlife. Potential of neighbourhood green spaces to function as urban wildlife habitats has not been optimized. This research investigates urban residents' responses to different dimension of attitudes toward common wildlife; and their needs for wildlife in the contact of sustainable living in the Klang Valley. The research, has sought to investigate through a combination of surveys and observations on residents' attitudes toward urban wildlife. The findings demonstrated selective preferences towards urban wildlife while residents displayed strong preferences toward naturalistic landscape elements compared to man-made landscape elements.